Surface pressure-area isotherms for Langmuir monolayers and a docking molecular orientation of perylene tetracarboxylic derivatives on a water surface - Constantino, C. J.L. [UNESP]; Antunes, P. A. [UNESP]; Oliveira, C. B.; Trsic, M.; Caracelli, I.; Aroca, R. R. (My University, 2004)
The surface pressure-molecular area (π-A) isotherms for Langmuir monolayers of four perylenetetracarboxylic (PTCD) derivatives, measured with varying subphase temperatures and compression speeds, are reported. The behavior of these PTCD derivatives at the water-air interface is modeled using the rigid docking method. This approach is the first attempt to model the molecular orientation of PTCD on the water surface to be compared with experimental Langmuir isotherms. Through this methodology, it would be possible to anticipate aggregation and determine if favorable spatial orientations of perylenes are generated on the water surface. The π-A isotherm experiments show that these molecules can support high surface pressures, indicating strong packing on the water surface and that the isotherms are compression speed independent but temperature dependent. The molecular orientation and stacking was further examined in Langmuir-Blodgett (LB) monolayers deposited onto glass and glass coated with Ag island films using UV-visible absorption and surface-enhanced fluorescence (SEF) measurements.
Keywords: Docking; Langmuir-Blodgett film; Molecular organization; Perylene; Surface-enhanced fluorescence; UV-vis